Preparation method of water-based iron ion battery positive electrode material, battery positive electrode material, water-based iron ion battery and application of water-based iron ion battery

The preparation of vanadium tetrasulfide cathode material through hydrothermal reaction and freeze-drying methods has solved the problem of poor circulation performance of the existing water-system iron ion battery cathode material, and achieved higher cycle stability and electrochemical performance.

CN119569116APending Publication Date: 2025-03-07SHIHEZI UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411782953.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The circulation performance of the existing water-system iron ion battery cathode material is poor and it is difficult to meet the practical application needs.

Method used

Vanadium tetrasulfide positive electrode material is prepared by hydrothermal reaction and freeze-drying to form a chain structure to improve electrochemical performance.

Benefits of technology

It improves the cycle stability and electrochemical performance of water-based iron ion batteries, and enhances the charge and discharge specific capacity and cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569116A_ABST
    Figure CN119569116A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a water-based iron ion battery positive electrode material, a battery positive electrode material, a water-based iron ion battery and application thereof, and belongs to the technical field of water-based iron ion batteries. The invention provides a preparation method of an aqueous iron ion battery positive electrode material, which comprises the following steps: 1) dissolving a vanadium source and a sulfur source in a solvent, and uniformly stirring to obtain a mixed solution; (2) carrying out hydrothermal reaction on the mixed solution obtained in the step (1), and after the reaction is completed, cleaning and carrying out suction filtration to obtain black powder; and 3) carrying out freeze drying on the black powder obtained in the step 2) to obtain the aqueous iron ion battery positive electrode material. The preparation method provided by the invention is simple, efficient and low in cost. The aqueous iron ion battery prepared from the battery positive electrode material is high in cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aqueous iron ion batteries, and in particular relates to a method for preparing an aqueous iron ion battery positive electrode material, a battery positive electrode material, an aqueous iron ion battery and applications thereof. Background Art

[0002] With the development of society, the problem of energy shortage has become increasingly prominent. Sustainable green and clean energy storage has become an urgent issue for researchers to break through. Rechargeable ion batteries are considered to be one of the most promising energy storage devices due to their low cost, abundant reserves, environmental protection, and strong safety. Among rechargeable batteries, lithium-ion batteries are the most mature and widely used type of rechargeable ion batteries. However, lithium-ion batteries face many problems, such as the scarcity, toxicity and flammability of lithium content, which have led to various sustainable development issues. In recent years, researchers have turned to the direction of safer and lower-cost multivalent ion batteries, such as Zn 2+ / Fe 2+ / Mg 2+ etc., to develop alternative and more ideal electrochemical energy storage devices.

[0003] Iron-ion batteries are one of the potential energy storage devices due to their low price, high theoretical specific capacity and other advantages. Compared with organic electrolytes, aqueous electrolytes are safer and more environmentally friendly. Aqueous iron-ion batteries are composed of iron metal negative electrodes, iron-containing aqueous electrolytes and positive electrode materials that can store iron ions. Rechargeable aqueous iron-ion batteries have the potential for large-scale energy storage applications and have gradually become the focus of researchers. They have great development advantages in the future battery market.

[0004] Iron-ion batteries have a high theoretical capacity. During discharge, the negative electrode Fe loses electrons and becomes Fe 2+ , and embedded into the positive electrode material. During charging, Fe 2+ The cathode material is embedded in the structure and migrates to the iron cathode. However, the cathode material research is single and the cycle performance is poor, which makes it difficult to fully meet the actual application needs. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a method for preparing an aqueous iron ion battery positive electrode material, a battery positive electrode material, an aqueous iron ion battery and applications thereof. The preparation method provided by the present invention is simple, efficient and low-cost. The aqueous iron ion battery prepared using the battery positive electrode material of the present invention has high cycle stability.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a positive electrode material for an aqueous iron ion battery, comprising the following steps:

[0008] 1) dissolving a vanadium source and a sulfur source in a solvent, stirring uniformly to obtain a mixed solution;

[0009] 2) subjecting the mixed solution obtained in step 1) to a hydrothermal reaction, and after the reaction is complete, washing and filtering to obtain a black powder;

[0010] 3) freeze-drying the black powder obtained in step 2) to obtain the positive electrode material for aqueous iron ion batteries.

[0011] Preferably, the vanadium source includes at least one of ammonium metavanadate, ammonium orthovanadate, vanadyl sulfate, vanadyl oxalate and vanadium pentoxide.

[0012] Preferably, the sulfur source includes at least one of thiourea, thioacetamide and cysteine.

[0013] Preferably, the molar ratio of the vanadium source to the sulfur source is 1:7-10.

[0014] Preferably, the temperature of the hydrothermal reaction is 160-180° C., and the time is 12-24 hours.

[0015] Preferably, the freeze-drying time is 12 to 24 hours.

[0016] The present invention also provides an aqueous iron ion battery positive electrode material prepared by the method for preparing the aqueous iron ion battery positive electrode material.

[0017] The present invention also provides an aqueous iron ion battery, comprising the above-mentioned aqueous iron ion battery positive electrode material, electrolyte and negative electrode material.

[0018] Preferably, the electrolyte includes at least one of ferrous trifluoromethanesulfonate, ferrous sulfate, ferrous chloride electrolyte, Fe(CF3SO3)2 gel electrolyte, and FeSO4 gel electrolyte.

[0019] The present invention also provides applications of the aqueous iron ion battery described above in electric vehicles, smart homes, wearable devices and large-scale energy storage systems.

[0020] The vanadium tetrasulfide material prepared by the preparation method of the positive electrode material of the aqueous iron ion battery provided by the present invention has a chain structure. The present invention uses vanadium and sulfur both of which have multi-electron reactions and can show higher electrochemical performance than general positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the XRD pattern of the positive electrode material of vanadium tetrasulfide of Example 1;

[0022] Figure 2This is a scanning electron microscope image of the vanadium tetrasulfide positive electrode material of Example 1;

[0023] Figure 3 CV diagram of the vanadium tetrasulfide cathode material in aqueous iron ion battery of Example 1;

[0024] Figure 4 The charge and discharge curve diagram of the aqueous iron ion battery of Example 1;

[0025] Figure 5 The cycle curve diagram of the aqueous iron ion battery of Example 1;

[0026] Figure 6 This is a cycle curve diagram of the aqueous iron ion battery of Example 2;

[0027] Figure 7 is a cycle curve diagram of the gel aqueous iron ion battery of Example 3;

[0028] Figure 8 This is a rate curve of the gel aqueous iron ion battery of Example 3. DETAILED DESCRIPTION

[0029] The present invention provides a method for preparing a positive electrode material for an aqueous iron ion battery, comprising the following steps:

[0030] 1) dissolving a vanadium source and a sulfur source in a solvent, stirring uniformly to obtain a mixed solution;

[0031] 2) subjecting the mixed solution obtained in step 1) to a hydrothermal reaction, and after the reaction is complete, washing and filtering to obtain a black powder;

[0032] 3) freeze-drying the black powder obtained in step 2) to obtain the positive electrode material for aqueous iron ion batteries.

[0033] In the present invention, the solvent of the vanadium source and the sulfur source is preferably at least one of distilled water, methanol, ethanol and butanol.

[0034] In the present invention, the vanadium source preferably includes at least one of ammonium metavanadate, ammonium orthovanadate, vanadyl sulfate, vanadyl oxalate and vanadium pentoxide.

[0035] In the present invention, the sulfur source preferably includes at least one of thiourea, thioacetamide and cysteine.

[0036] The present invention has no special limitation on the sources of the vanadium source and the sulfur source, and conventional commercial products in the art may be used.

[0037] In the present invention, the molar ratio of the vanadium source to the sulfur source is preferably 1:7-10.

[0038] In the present invention, the water is preferably distilled water.

[0039] In the present invention, the hydrothermal reaction is preferably carried out in a hydrothermal reactor.

[0040] In the present invention, the temperature of the hydrothermal reaction is preferably 160-180° C., and the time is preferably 12-24 hours.

[0041] In the present invention, the solvents used for the cleaning are preferably water and ethanol, and the cleaning method is preferably washing with water and ethanol alternately, preferably at least three times.

[0042] In the present invention, the freeze drying is preferably carried out in a freeze drying agent, and the freeze drying time is preferably 12 to 24 hours.

[0043] The present invention also provides an aqueous iron ion battery positive electrode material prepared by the method for preparing the aqueous iron ion battery positive electrode material.

[0044] In the present invention, the aqueous iron ion battery positive electrode material is preferably a vanadium tetrasulfide positive electrode material.

[0045] The present invention also provides an aqueous iron ion battery, comprising the above-mentioned aqueous iron ion battery positive electrode material, electrolyte and negative electrode material.

[0046] In the present invention, the electrolyte preferably includes at least one of ferrous trifluoromethanesulfonate, ferrous sulfate, ferrous chloride electrolyte, Fe(CF3SO3)2 gel electrolyte, and FeSO4 gel electrolyte.

[0047] In the present invention, the concentration of the ferrous trifluoromethanesulfonate, ferrous sulfate and ferrous chloride electrolytes is preferably 2 mol / L; the concentration of the Fe(CF3SO3)2 gel electrolyte and FeSO4 gel electrolyte is preferably 1 mol / L.

[0048] In the present invention, the negative electrode of the aqueous iron ion battery is preferably made of iron foil.

[0049] The present invention also provides applications of the aqueous iron ion battery described above in electric vehicles, smart homes, wearable devices and large-scale energy storage systems.

[0050] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0051] Example 1

[0052] The invention discloses an aqueous iron ion battery, wherein the positive electrode comprises a vanadium tetrasulfide material, the negative electrode is made of an iron foil, and the electrolyte is an aqueous solution of ferrous trifluoromethanesulfonate.

[0053] The preparation method of the aqueous iron ion battery comprises the following steps:

[0054] 1) Dissolve ammonium metavanadate (NH4VO3) and thioacetamide (TAA) in distilled water at a molar ratio of 1:10, stir for 30 minutes to form a uniform mixed solution; put the obtained solution into a 100mL hydrothermal reactor, react in a forced air drying oven at 180°C for 24 hours; and wash alternately with deionized water and ethanol for at least three times, and filter;

[0055] 2) The obtained product is placed in a freeze dryer and freeze-dried for more than 12 hours to obtain a vanadium tetrasulfide material;

[0056] 3) Dispersing vanadium tetrasulfide material, Ketjen black and polyvinylidene fluoride in N-methylpyrrolidone at a mass ratio of 7:2:1, coating on a titanium mesh, drying in a vacuum drying oven at 80°C for 12 hours, and cutting to obtain a battery electrode;

[0057] 4) In a clean indoor environment, the battery electrode of step 3) is used as the positive electrode, the iron foil is used as the negative electrode, ferrous trifluoromethanesulfonate with a concentration of 2 mol / L is used as the electrolyte, and glass fiber is used as the separator, and a CR2032 button battery is encapsulated to obtain an aqueous iron ion battery.

[0058] Performance Test:

[0059] 1) The X-ray diffraction (XRD) pattern of the vanadium tetrasulfide cathode material in this embodiment is as follows: Figure 1 As shown. Figure 1 It can be seen that the vanadium tetrasulfide material in this embodiment is consistent with the standard card and is a pure phase vanadium tetrasulfide positive electrode material.

[0060] 2) The scanning electron microscope (SEM) image and element distribution of the vanadium tetrasulfide positive electrode material in this embodiment are as follows: Figure 2 As shown. Figure 2 It can be seen that the positive electrode material of vanadium tetrasulfide in this example is a cluster material with a diameter of 3 μm formed by nano-sheet accumulation.

[0061] 3) The CV graphs of the aqueous iron ion battery of this embodiment at voltages of 0.01 to 1.2 V and different scan rates are as follows: Figure 3 shown.

[0062] 4) The charge and discharge curves of the aqueous iron ion battery of this embodiment at a voltage of 0.01 to 1.2 V and a current density of 200 mA / g are as follows: Figure 4 As shown. Figure 4 It can be seen that the charge-discharge specific capacity of the aqueous iron ion battery of this embodiment is relatively high.

[0063] 5) The curve of the aqueous iron ion battery of this embodiment after 100 cycles at a voltage of 0.01 to 1.2 V and a current density of 200 mA / g is as follows: Figure 5 As shown. Figure 5 It can be seen that the aqueous iron ion battery of this embodiment can maintain a capacity of 120 mAh / g after 100 cycles at a current density of 200 mA / g.

[0064] Example 2

[0065] The invention discloses an aqueous iron ion battery, wherein the positive electrode material comprises a vanadium tetrasulfide positive electrode material, the negative electrode is made of iron foil, and the electrolyte is an aqueous solution of ferrous trifluoromethanesulfonate.

[0066] The preparation method of the aqueous iron ion battery comprises the following steps:

[0067] 1) Dissolve ammonium metavanadate (NH4VO3) and thiourea (TU) in distilled water at a molar ratio of 1:10, stir for 30 minutes to form a uniform mixed solution; put the obtained solution into a 100mL hydrothermal reactor, react at 180°C in a forced air drying oven for 24 hours; and wash with deionized water and ethanol alternately for at least three times, and filter;

[0068] 2) The obtained product is placed in a freeze dryer and freeze-dried for more than 12 hours to obtain a vanadium tetrasulfide material;

[0069] 3) Dispersing vanadium tetrasulfide material, Ketjen black and polyvinylidene fluoride in N-methylpyrrolidone at a mass ratio of 7:2:1, coating on a titanium mesh, drying in a vacuum drying oven at 80°C for 12 hours, and cutting to obtain a battery electrode;

[0070] 4) In a clean indoor environment, the battery electrode of step 3) is used as the positive electrode, the iron foil is used as the negative electrode, ferrous trifluoromethanesulfonate with a concentration of 2 mol / L is used as the electrolyte, and glass fiber is used as the separator, and a CR2032 button battery is encapsulated to obtain an aqueous iron ion battery.

[0071] Performance Test:

[0072] 1) The charge and discharge curves of the aqueous iron ion battery of this embodiment at a voltage of 0.01 to 1.2 V and a current density of 200 mA / g are as follows: Figure 6 As shown. Figure 6 It can be seen that the charge-discharge specific capacity of the aqueous iron ion battery of this embodiment is relatively high.

[0073] Example 3

[0074] A gel water iron ion battery, wherein the positive electrode comprises a vanadium tetrasulfide positive electrode material, the negative electrode is made of iron foil, and the electrolyte comprises a ferrous trifluoromethanesulfonate gel electrolyte formed by immersing in an aqueous solution of ferrous trifluoromethanesulfonate.

[0075] The preparation method of the above-mentioned gel aqueous iron ion battery comprises the following steps:

[0076] 1) Dissolve ammonium metavanadate (NH4VO3) and thioacetamide (TAA) in distilled water at a molar ratio of 1:10, stir for 30 minutes to form a uniform mixed solution; put the obtained solution into a 100mL hydrothermal reactor, react in a forced air drying oven at 180°C for 24 hours; and wash alternately with deionized water and ethanol for at least three times, and filter;

[0077] 2) The obtained product is placed in a freeze dryer and freeze-dried for more than 12 hours to obtain a vanadium tetrasulfide material;

[0078] 3) Dispersing vanadium tetrasulfide material, Ketjen black and polyvinylidene fluoride in N-methylpyrrolidone at a mass ratio of 7:2:1, coating on a titanium mesh, drying in a vacuum drying oven at 80°C for 12 hours, and cutting to obtain a battery electrode;

[0079] 4) The gel formed by polypropylene imine is immersed in a 1 mol / L ferrous trifluoromethanesulfonate aqueous solution for more than 12 hours, cut into appropriate sizes for use as an electrolyte and a separator, and packaged into a CR2032 button cell to obtain a gel aqueous iron ion battery.

[0080] Performance Test:

[0081] 1) The charge and discharge curves of the aqueous gel iron ion battery of this embodiment under the conditions of voltage of 0.01V to 1.2V and current density of 200mA / g are as follows: Figure 7 shown.

[0082] 2) The rate performance of the aqueous gel iron ion battery of this embodiment at voltages of 0.01V to 1.2V and different current densities is as follows: Figure 8 shown.

[0083] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a positive electrode material for an aqueous iron ion battery, characterized in that: The following steps are involved: 1) dissolving a vanadium source and a sulfur source in a solvent, stirring uniformly to obtain a mixed solution; 2) subjecting the mixed solution obtained in step 1) to a hydrothermal reaction, and after the reaction is complete, washing and filtering to obtain a black powder; 3) freeze-drying the black powder obtained in step 2) to obtain the positive electrode material for aqueous iron ion batteries.

2. The method for preparing a positive electrode material for an aqueous iron ion battery according to claim 1, characterized in that: The vanadium source includes at least one of ammonium metavanadate, ammonium orthovanadate, vanadyl sulfate, vanadyl oxalate and vanadium pentoxide.

3. The method for preparing a positive electrode material for an aqueous iron ion battery according to claim 1, characterized in that: The sulfur source includes at least one of thiourea, thioacetamide and cysteine.

4. The method for preparing a positive electrode material for an aqueous iron ion battery according to claim 1, characterized in that: In the step 1), the molar ratio of the vanadium source to the sulfur source is 1:7-10.

5. The method for preparing a positive electrode material for an aqueous iron ion battery according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step 2) is 160-180° C. and the time is 12-24 hours.

6. The method for preparing a positive electrode material for an aqueous iron ion battery according to claim 1, characterized in that: The freeze-drying time in step 3) is 12 to 24 hours.

7. Aqueous iron ion battery positive electrode material prepared by the method for preparing an aqueous iron ion battery positive electrode material according to any one of claims 1 to 6.

8. An aqueous iron ion battery, characterized in that: It comprises the positive electrode material, electrolyte and negative electrode material of the aqueous iron ion battery as described in claim 7.

9. An aqueous iron ion battery according to claim 8, characterized in that: The electrolyte includes at least one of ferrous trifluoromethanesulfonate, ferrous sulfate, ferrous chloride electrolyte, Fe(CF3SO3)2 gel electrolyte, and FeSO4 gel electrolyte.

10. Application of the aqueous iron ion battery according to claim 8 in electric vehicles, smart homes, wearable devices and large-scale energy storage systems.